2020
DOI: 10.1097/md.0000000000018730
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic acid use is associated with significant risk of morbidity and mortality in infants with cholestasis

Abstract: The off-label use of medications is a “right” for pediatricians, owing to lack of enough safety and effectiveness drug trials in pediatric age group. Pediatricians have to rely on their personal judicial use of medications in children. We studied off-label use of ursodeoxycholic acid (UDCA) retrospectively during 2005 to 2015 among those who attended the Pediatic Hepatology Unit, Cairo University. We analyzed data of 779 neonates and infants with cholestasis. 15% dropped out. Males comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…However, authors of recent work have raised alarms about the use of ursodiol in infants, including an association with increased mortality. 33 Both of our patients and many of the published cases (Table 1) received IVIg. IVIg remains a recommended intervention for HDFN and hyperbilirubinemia, 34 although there are limited data supporting its efficacy for HDFN.…”
Section: Discussionmentioning
confidence: 69%
“…However, authors of recent work have raised alarms about the use of ursodiol in infants, including an association with increased mortality. 33 Both of our patients and many of the published cases (Table 1) received IVIg. IVIg remains a recommended intervention for HDFN and hyperbilirubinemia, 34 although there are limited data supporting its efficacy for HDFN.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, a long-term, double-blind, randomized controlled trial found that the risk of developing cirrhosis, varicose veins, bile duct cancer, liver transplantation and death was twice in patients receiving high-dose UDCA (28 to 30 mg/kg/d) compared with patients receiving the placebo [ 50 , 51 ]. There was no long-term, double-blind, randomized controlled trial conducted to evaluate the effect of UDCA on the long-term prognosis of children with cholestasis, but a retrospective study has shown that UDCA (15 to 40 mg/kg/d) had no benefit to neonates and infants with cholestasis (obstructive and non-obstructive) and put them at a higher risk of treatment failure [ 15 , 16 ]. And it was associated with disease progression, severe complications (hepatocyte failure, ascites, vanishing bile duct syndrome, and so forth.)…”
Section: Discussionmentioning
confidence: 99%
“…However, some researchers believed that UDCA was ineffective and unsafe in infants and neonates with cholestasis and might be associated with severe complications (cirrhosis, hepatocyte failure, and so forth. ), disease progression and death, especially when taking higher doses (20–40 mg/kg) /d) [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The risks that occur in the prolonged administration of ursodeoxycholic acid are beyond the scope of this report. The recent report by Kotb [20] of the increased mortality in a large group of infants and children receiving ursodeoxycholic acid for liver disease compared with a control group should alert physicians to currently unaddressed problems with its prolonged use.…”
Section: Plasma Alkaline Phosphatase and Cholestasismentioning
confidence: 99%